The influence of the family in the development of talent in sport - Côté, J. (The Sport Psychologist, 1999)
Examined patterns in the dynamics of families of talented athletes throughout their development in sport. Four families, including 3 families of elite rowers and 1 family of an elite tennis player, were examined. The framework provided by K. A. Ericsson et al (1993) to explain expert performance served as the theoretical basis for the study. Ericsson et al suggested that the acquisition of expert performance involves operating within 3 types of constraints: motivational, effort, and resource. In-depth interviews were conducted with each athlete, parent, and sibling to explore how they have dealt with these 3 constraints. A total of 15 individual interviews were conducted. Results permitted the identification of 3 phases of participation from early childhood to late adolescence: the sampling years, the specializing years, and the investment years. The dynamics of the family in each of these phases of development is discussed.